Detection of gyrA Mutation Among Clinical Isolates of Campylobacter jejuni Isolated in Egypt by MAMA-PCR - Mayar Maged Said; Hanan El-Mohamady; Fawkia M. El-Beih; David M. Rockabrand; Tharwat F. Ismail; Marshall R. Monteville; Salwa F. Ahmed; John D. Klena; Mohamed S. Salama (Journal of Infection in Developing Countries)
Introduction: Campylobacter spp are the major cause of enteritis in humans and more than 90% of reported infections are caused by Campylobacter jejuni. Fluoroquinolones such as ciprofloxacin are the antibiotics of choice for treatment.  An increase in the frequency of ciprofloxacin-resistant Campylobacter has been reported globally due to a single base mutation (C-257 to T) in codon 86 of the quinolone resistance determining region (QRDR) of the gyrA gene altering the amino acid sequence from threonine at position 86 to isoleucine (Thr-86 to Ile).